A design modification for a quadrotor UAV: modeling, control and implementation. (2nd January 2019) - Badr, Sherif; Mehrez, Omar; Kabeel, A. E.
ABSTRACT: Conventional quadrotor unmanned aerial vehicles have crucial underactuation limitations. This appears in the coupling between the roll angle and movement along the y -direction, and between the pitch angle and movement along the x -direction. The quadrotor capability of hovering with either roll or pitch angle is restricted due to these limitations. In this paper, a design modification, with experimental verification, is proposed in order to increase the quadrotor degrees of freedom and improve its hovering capability. Four additional rotations for the propellers about the axes perpendicular to the arms grant overactuated system. It could be used to make a horizontal movement with zero inclination angle which is followed in this work as an example for the skills acquired by the quadrotor due to the proposed design. Choosing different tilting axes, rather than the mostly considered ones in previous work which are about the ones along the arms, enhances the advantages of this modification. The benefits are to increase the degrees of freedom and improve the hovering of the quadrotor as well. A PID controller is utilized for practical implementation of the proposed design. Simulation and experimental results show the validity of the proposed design. GRAPHICAL ABSTRACT: